Tulaberry Plaza : leasing decisions in commercial real estate - Furfine, Craig (London : Kellogg School of Management, 2019)
In January 2019, Benedict Clarke needed to address the vacancies at retail shopping center Tulaberry Plaza in Southeast Orlando. The rise in online shopping forced Tulaberry's anchor tenant into bankruptcy and weakened the outlook for retail more generally. Clarke must devise a plan that presents the most logical and profitable way forward for the shopping center. The case asks students to make leasing decisions from the perspective of the property owner, Clarke, giving them an appreciation for both the quantitative and qualitative factors that influence optimal leasing decisions.
Originally Published InFurfine, C. (2019). Tulaberry Plaza: Leasing Decisions in Commercial Real Estate. 5-318-502. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Real estate business -- Case studies; Real estate investment -- Case studies; Shopping centers -- Case studies